VALUE FOR MONEY IN E-LEARNING OUTCOMES: Received: 15th July 2025, Revised: 27th November 2025, Accepted: 28th November 2025, 01st December 2025, Date of Publication: 04th December 2025 - Rabab Hamdan; Wajeeh Daher (PUPIL: International Journal of Teaching, Education and Learning, 2025)
The purpose of this study was to examine how the "Value for Money" (VfM) principle, a crucial element of international quality standards in higher education, is applied to educational outcomes. In order to promote positive transformation among academic staff and students, it focuses on assessing the balance between financial expenditure and the efficacy of resource utilization. Three Palestinian universities participated in the study, which used qualitative information gathered from interviews. A purposive sample of six employees from e-learning centers was included in the study population, which included 13 members from e-learning administration departments. With an emphasis on the fourth standard, "Value for Money," which was modified for the context of e-learning in Palestinian universities, the interview protocol was created using international quality assurance standards in higher education. The results showed that there are major obstacles to raising the caliber of educational outputs in order to keep up with the quick development of educational products around the world. Limited funding for infrastructure development and maintenance, attempts to improve network performance in the face of ongoing budget deficits, and wage cuts in certain institutions to support e-learning programs were among the main problems. Based on financial limitations, universities grant network access with regard to data security. Many institutions rely on free and open-source software because of their limited funding. To improve self-sustainability, the study suggests investing in university facilities and looking into alternate funding sources. In order to reduce the risks associated with unanticipated events, it also promotes fortifying the infrastructure for online education and establishing alliances with insurance providers.